2018
DOI: 10.14245/ns.1836140.070
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of the Use of Salvaged Blood in Metastatic Spine Tumour Surgery

Abstract: To review the current status of salvaged blood transfusion (SBT) in metastatic spine tumour surgery (MSTS), with regard to its safety and efficacy, contraindications, and adverse effects. We also aimed to establish that the safety and adverse event profile of SBT is comparable and at least equal to that of allogeneic blood transfusion. MEDLINE and Scopus were used to search for relevant articles, based on keywords such as “cancer surgery,” “salvaged blood,” and “circulating tumor cells.” We found 159 articles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 89 publications
(119 reference statements)
0
15
0
1
Order By: Relevance
“…Special filters for their elimination increase the cost and affect the flow conditions during retransfusion, resulting in the activation of the complement system. In the case of immunosuppressed or cancer patients, leucodepletion of these concentrates could be considered for safety reasons during major orthopedic surgery (18) , (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Special filters for their elimination increase the cost and affect the flow conditions during retransfusion, resulting in the activation of the complement system. In the case of immunosuppressed or cancer patients, leucodepletion of these concentrates could be considered for safety reasons during major orthopedic surgery (18) , (19) .…”
Section: Discussionmentioning
confidence: 99%
“…An extension of this review concluded clinical safety of ICS for this indication, providing evidence for decreased risk for postoperative infections and tumour recurrence, and supported the use of ICS even without LDF in metastatic spinal tumour surgery. This is still controversial for many clinical practitioners [47].…”
Section: Metastatic Spinal Tumour Surgerymentioning
confidence: 99%
“…Evaluation tools for this were regression, uni-/multivariate analysis, or sensitivity/specificity. We analyzed accuracy of SINS category divided into two groups (SINS, 0-6 vs. 7-18) or three groups (SINS, 0-6 vs. 7-12 vs. [13][14][15][16][17][18]. We also evaluated accuracy of each component of the SINS (location, pain, bone lesion, radiologic alignment, body collapse, and posterolateral involvement) if data were available.…”
Section: Search Strategy and Study Selection Criteriamentioning
confidence: 99%
“…In the past, external beam radiotherapy had been the cornerstone of treatment for painful spinal metastases [ 35 ]. Since the study of Patchell et al [ 26 ] in 2005, direct surgical decompression and stabilization in patients with metastatic epidural spinal cord compression has been feasible and demonstrated better outcomes [ 14 , 18 , 25 , 38 ]. As surgical outcomes have been enhanced, consultations for surgery have increased to include spinal metastasis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%